Predicting the fraud volume in the advent of internet enabled handheld devices - Zammarah, Nuha Abdullah; Shah , Asadullah (2015)
Online banking has been growing tremendously in the recent years due to the vast development of internet applications on both computer and handheld devices. However, this advancement is faced by equally growing fraud attacks over the last decade. Customer awareness and vendor awareness are considered important factors in the study of fraud attacks volume increase. Moreover, more stringent security standards and multiple defensive security lines have been proposed to reduce the fraud attack cases. Nevertheless, fraud attack cases are showing a relentless increase in the past decade. This increase is attributed to the development of new attack methods and the evolution of new technologies which form new channels for fraudulent to attack. This paper addresses the fraud attack from a new perspective. In this paper, Adaptive Neuro-Fuzzy Inference System (ANFIS) is used to associate the increase in both computers based and handheld devices based internet usage and the fraud attack volume. The system will be trained from data collected in the past decade and then used to predict the effect of internet usage rate on the fraud attack volume for different age groups as well as the total fraud volume in the future. Three different scenarios in this study are considered to be addressing the effect of personal computer operating system, mobile operating system and android attack rate on the fraud volume. Results show that fraud volume would increase with the increase of android attack rate and would decrease with the increase of personal computer and mobile operating system usage rate. Therefore, the main focus on the awareness about fraud should be given to the mobile operating system users who are aged between 20-39 years old and above 70 years old as they cause increasing in the fraud.